2017
DOI: 10.1159/000486011
|View full text |Cite
|
Sign up to set email alerts
|

Early Markers of Cardiovascular Risk in Autosomal Dominant Polycystic Kidney Disease

Abstract: Background/Aims: Cardiovascular disease is the most frequent cause of morbidity and mortality in autosomal dominant polycystic kidney disease (ADPKD) patients, often before the onset of renal failure, and the pathogenetic mechanism is not yet well elucidated. The aim of the study was to identify early and noninvasive markers of cardiovascular risk in young ADPKD patients, in the early stages of disease. Methods: A total of 26 patients with ADPKD and 24 control group, matched for age and sex, were enrolled, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…Pathologic rates of ABI values were lower in patients with ADPKD than in CKDoe, and similar to controls without CKD. A previous study showed a normal ABI value in patients with ADPKD with an eGFR > 60 mL/min [30].…”
Section: Discussionmentioning
confidence: 87%
“…Pathologic rates of ABI values were lower in patients with ADPKD than in CKDoe, and similar to controls without CKD. A previous study showed a normal ABI value in patients with ADPKD with an eGFR > 60 mL/min [30].…”
Section: Discussionmentioning
confidence: 87%
“…Subsequently, five studies were excluded as two of them did not contain a control group, 29,30 two studies used different procedures for the evaluation of vascular stiffness 31,32 (ie nitroglycerin‐induced dilatation, hand skin heating test) while one article 33 represented a partial duplicate of a study that was already included in the present review. As a result, a total of 27 studies 34‐60 were included, comprising 1967 individuals (1141 ADPKD patients and 826 healthy controls).…”
Section: Resultsmentioning
confidence: 99%
“…Higher baseline serum uric acid in ADPKD patients has also been retrospectively associated with a high risk of ESRD [40] and uric acid is increased in the urine of a juvenile cystic mouse model [37]. One study found an association between increased serum uric acid and decreased creatinine clearance rate in ADPKD, without any evidence of increased uric acid production [41], a second study found ADPKD patients had a higher incidence of hyperuricemia than patients with CKD or normal renal function despite all groups having normal rates of uric acid excretion [29] and a third study found ADPKD patients with normal renal function had elevated serum uric acid [42]. Neither study found evidence of increased uric acid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between ADPKD with normal kidney function and healthy patients found only 3 components of metabolic syndrome were increased in ADPKD patients, namely hypertension, fasting glycemia and abdominal obesity [47]. A different study of young ADPKD patients with normal renal function found increased insulin resistance, inflammation and low density lipoprotein (LDL) in ADPKD [42]. A study in Southern India found ADPKD patients of a wide variety of ages had moderately increased plasma triglycerides, LDL and very low density lipoprotein (VLDL), and a ~ 50% reduction in high density lipoprotein (HDL) compared to healthy controls [48].…”
Section: Discussionmentioning
confidence: 99%